2022
DOI: 10.1111/cts.13266
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of PDE4B (phosphodiesterase‐4B) in neglected Native Americans: Implications for cancer pharmacogenetics

Abstract: PDE4B (phosphodiesterase-4B) has an important role in cancer and in pharmacology of some disorders, such as inflammatory diseases. Remarkably in Native | 1401 POPULATION GENETICS OF PDE4B IN NATIVE AMERICANS Federal do Triângulo Mineiro,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, some population groups remain underrepresented in these types of investigations, such as Native American populations. Recently, some efforts have been made to include genetic information about allelic frequencies of Native American populations and their influence on susceptibility to diseases, such as severe forms of COVID-19 [ 23 ], psychological disorders [ 24 ], oncological diseases [ 25 , 26 ], and also on different types of pharmacological treatments [ 12 , 13 , 27 , 28 ]. Most of these studies are focused on one or a few group of genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some population groups remain underrepresented in these types of investigations, such as Native American populations. Recently, some efforts have been made to include genetic information about allelic frequencies of Native American populations and their influence on susceptibility to diseases, such as severe forms of COVID-19 [ 23 ], psychological disorders [ 24 ], oncological diseases [ 25 , 26 ], and also on different types of pharmacological treatments [ 12 , 13 , 27 , 28 ]. Most of these studies are focused on one or a few group of genes.…”
Section: Discussionmentioning
confidence: 99%
“…ALL is characterized by an excess of immature lymphocytes, which are more common in children between the ages of 2 and 5 years than in adults ( Medinger et al, 2019 ). Rennan Garcias Moreira et al (2022) found that PDE4B promotes tumor angiogenesis in ALL. Notably, in Native Americans, the PDE4B allele rs6683977 variant is associated with ALL relapse ( Chen et al, 2020 ).…”
Section: Functional Regulatory Role Of Phosphodiesterase 4b In Human ...mentioning
confidence: 99%